Analisis Multi Raster SRTM, Radarsat dan Landsat untuk Karakterisisasi Morfo-struktur dari Geometri Sesar di Daerah Binuang, Kalimantan Selatan - Jamal, Jamal; Sulaksana, Nana; Sukiyah, Emi; Andriana Sendjaja, Yoga (Jurnal Geologi dan Sumberdaya Mineral, 2019)
The Binuang area and its surroundings are genetically structural landforms which characterized by cuesta ridge line with curve lineaments pattern on northeast-southwest direction. Geomorphological approach were carried out to determine structural geometry of geological surface using qualitative and quantitative approach on multiple map analysis of remote sensing data. The result of quantitative analysis on elevation data are used to classify heights, slope shape and steepness, lineaments, drainage, and slope aspect. Optical images were classified to determine lithological pattern and boundaries through analysis of band ratios, decorrelation stretch, principal component, and spatial enhancement. The research area are classified into eight class of structural landforms, depicting deformations that occured in western flank of Meratus Mountains. The surface pattern indicates the influence of compressional stress, shown by fold belt with longitudinal characteristic and fault-bounded anticlines on northeast-southwest axis. The formation of main structure pattern on research area was compared with that on strike-slip fault analog model. The resulting correlation factor, R=0.932, shows that both of them are highly correlated. In conclusion, surface structure can possibly form another variation of thrusted mountain belt, such as thrust-dominated restraining bends.Keywords: landsat, SRTM, morphostructure, morphometry, rhomboidal pattern, Meratus.